Penyelarasan Rencana Biaya dengan Sumber Pendanaan Organisasi Pendidikan Islam - Tanto Prima; Ummi Mardiyah (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
The alignment of budget planning with funding sources is a crucial aspect of financial management in Islamic educational organizations to ensure operational sustainability and improve the quality of educational services. This study aims to analyze strategies that can be implemented in drafting and adjusting budget plans with various funding sources, such as government funds, zakat, infaq, waqf, community donations, and student contributions. This research employs the library research method, which involves collecting and analyzing various literature related to Islamic educational financial management. The results indicate that the principles of efficiency, effectiveness, transparency, and accountability must be applied in managing educational funds to ensure optimal budget utilization. One of the key indicators for maintaining financial balance is the budget balance ratio, which measures the extent to which an organization’s revenue can cover its expenditures. If the ratio reaches or exceeds 100%, it indicates a surplus that can be allocated for institutional development. However, if the ratio is below 100%, a deficit occurs that must be addressed immediately through cost efficiency strategies, diversification of funding sources, and optimization of productive waqf assets. This study emphasizes that a systematic and sustainable financial strategy is essential for maintaining the financial stability of Islamic educational organizations. By implementing well-structured budget planning, strict supervision, and diversified funding sources, organizations can ensure financial sustainability and enhance the overall quality of Islamic education.